Sedimentary characteristics of post-uplift basins in foreland basin system: a case study of Jurassic Sangonghe Formation in hinterland of Junggar Basin - Xiang LI; Yajie DING; Junfei LI; Gang XU; Yadong JING (Shiyou shiyan dizhi)
Foreland basins are rich in oil and gas resources, with most being concentrated in the foredeep zone. However, as breakthroughs in oil and gas exploration in post-uplift basins have been made, these types of basins gradually become a research hotspot. The hinterland of the Junggar Basin is a post-uplift basin, and the Jurassic Sangonghe Formation is an important oil and gas-bearing layer in this area. However, there is still a significant debate about the types of sedimentary facies in this formation. With the progress of exploration and the continuous enrichment of geological data, the types and evolution of the sedimentary facies in the Sangonghe Formation have gradually become clearer. To clarify the sedimentary facies types, distribution, and the differences from the foredeep zone in the post-uplift basins of the foreland basin system, the study analyzed geological profiles, cores, well logging, seismic data, and analytical test results. It provided a detailed analysis of the sedimentary facies types, distribution characteristics, and controlling factors of the Sangonghe Formation. The sedimentary facies types of the Sangonghe Formation include braided river delta facies, sublacustrine fan facies, and lacustrine facies. The braided river delta facies are further subdivided into the plain and front subfacies, which are mainly distributed in the Shixi and Mobei areas. The sublacustrine fan facies are mainly distributed in the west sag of well 1 in the basin, characterized by Bouma sequences, with "A" and "B" segments being mostly common. The sediment source for these fans came from the braided river delta in the eastern part of the study area. During the sedimentary period of the Sangonghe Formation, there were three sources in the study area, instead of only two sources from the northwest and northeast as previously believed. Stable heavy mineral analysis showed that the W36 sublacustrine fan was affected by the northeastern sediment source, while the W46 sublacustrine fan was affected by the southeastern source. Sediments in the foredeep zone of the foreland basin were coarse, with simple sedimentary facies types and structural oil and gas reservoirs as the primary trap types. However, sediments in the post-uplift basin had finer grain sizes, with more varied sedimentary facies types, and were dominated by tectonic-lithologic and lithologic oil and gas reservoirs.